Integration of Electrochemistry with Ultra-Performance Liquid Chromatography/Mass Spectrometry. Issue 3 (June 2015) - Cai, Yi; Zheng, Qiuling; Liu, Yong; Helmy, Roy; Loo, Joseph A.; Chen, Hao
This study presents the development of ultra-performance liquid chromatography (UPLC) mass spectrometry (MS) combined with electrochemistry (EC) for the first time and its application for the structural analysis of proteins/peptides that contain disulfide bonds. In our approach, a protein/peptide mixture sample undergoes a fast UPLC separation and subsequent electrochemical reduction in an electrochemical flow cell followed by online MS and tandem mass spectrometry (MS/MS) analyses. The electrochemical cell is coupled to the mass spectrometer using our recently developed desorption electrospray ionization (DESI) interface. Using this UPLC/EC/DESI-MS method, peptides that contain disulfide bonds can be differentiated from those without disulfide bonds, as the former are electroactive and reducible. MS/MS analysis of the disulfide-reduced peptide ions provides increased information on the sequence and disulfide-linkage pattern. In a reactive DESI-MS detection experiment in which a supercharging reagent was used to dope the DESI spray solvent, increased charging was obtained for the UPLC-separated proteins. Strikingly, upon online electrolytic reduction, supercharged proteins (e.g., α -lactalbumin) showed even higher charging, which will be useful in top-down protein structure MS analysis as increased charges are known to promote protein ion dissociation. Also, the separation speed and sensitivity are enhanced by approximately 1∼2 orders of magnitude by using UPLC for the liquid chromatography (LC)/EC/MS platform, in comparison to the previously used high-performance liquid chromatography (HPLC). This UPLC/EC/DESI-MS method combines the power of fast UPLC separation, fast electrochemical conversion, and online MS structural analysis for a potentially valuable tool for proteomics research and bioanalysis.